África e as viagens da paz de João Lourenço num heartland em constante crise - Almeida, E. C. (Figuras & Negócios, 2024)
Abstract: The Great Lakes Region (GLR), particularly the Democratic Republic of Congo (DRC) and Rwanda, has been marked by complex and prolonged conflicts. The diplomatic efforts of João Lourenço, President of Angola, have been crucial in the pursuit of peaceful and sustainable solutions to the tensions in the region, especially regarding the rebel group M-23, which has caused significant instability in areas of eastern DRC. This text/essay, taking advantage of the recent Ceasefire Agreement of July 30, 2024, will examine President João Lourenço's diplomatic initiatives, including the Luanda Peace Protocols of 2019 and 2022 and the aforementioned recent ceasefire agreement that came into effect on August 4, 2024, as well as analyze M-23's response to these agreements.